Investigation of Prognostic Biomarkers in Advanced Stage Ovarian Cancer - Ateş, Sinan; Varol, Gülizar Füsun (The European Research Journal, 2026)
Objectives: Ovarian cancer is a fatal disease originating from egg cells in the female reproductive system. It is the most lethal of gynecological cancers, accounting for 4% of all cancers in women and 25% of female reproductive system cancers. Inflammation plays a significant role in the development of ovarian cancer, as in many diseases. In this study, we aimed to investigate the effects of biomarkers on disease monitoring and prognosis in patients with advanced ovarian cancer. Methods: This study included patients who underwent surgery for advanced-stage ovarian cancer at the Trakya University Gynecology and Obstetrics Clinic between February 2006 and July 2012. Twenty-nine consecutive patients with long-term follow-up were included in the study. Twenty-nine patients with ovarian cancer diagnosed as stage III and stage IV according to International Federation of Gynecology and Obstetrics (FIGO). Twelve healthy postmenopausal patients were also included as a control group. In the study group, all of these patients underwent surgical treatment. Standard surgical treatment for all ovarian cancer patients included total abdominal hysterectomy, bilateral salpingo-oophorectomy, and omentectomy as cytoreduction surgery, to minimize residual tumor. Results: Mean age of the study group was 52.6±8.8 (range: 36-77) years. Twenty-three (79%) were evaluated as stage III, and 6 patients were evaluated as stage IV. The ages of the control group ranged from 49 to 72 (mean: 54.3±8.1 years). The two groups were similar in terms of age (P=0.467). CA-125, transforming growth factor- beta (TGF-β), and C-reactive protein (CRP) values were statistically significantly higher in the patient group (P<0.001, for all variables). Omental involvement was positive in 21 (72%) patients. When patients were evaluated for subdiaphragmatic involvement, subdiaphragmatic peritoneal involvement was detected in 14 (49%) patients. Recurrence was detected in 20 (66%) of the 29 patients included in the study. Recurrence was detected in all 6 patients evaluated as stage IV, for a maximum of 77 months. Conclusions: Advanced-stage ovarian cancer seems associated with inflammatory markers. We can also suggest that these markers should be considered in patients’ clinical follow-up.